2016
DOI: 10.12816/0028234
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Immunohistochemical Expression of Moesin , Cytokeratin 14 and MMP7 in Oral Squamous Cell Carcinoma and Oral Verrucous Carcinoma

Abstract: Background: Squamous cell carcinoma (SCC) is the most prevalent malignant neoplasm of the oral cavity that exhibits certain histological variations. Verrucous carcinoma (VC) is an uncommon exophytic low-grade welldifferentiated variant of SCC. Cellular differentiation and morphology play important roles in cell functions and maintenance of structural integrity .As the cancer is a malignant process in which disorder of the cell growth and behavior occurs, such changes may differ in different tumor types and wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Most studies in this review found that Moesin was strongly associated with the histopathological grading for cancer[ 6 8 9 16 18 26 ] but was not elicited in a study[ 17 ] done in Baghdad where no statistical significance was elicited between the expression of Moesin and its association with the histopathological grading in OSCC cases. In a study[ 26 ] on laryngeal squamous cell carcinoma (LSCC), Moesin expression did not show any association with the advanced clinical staging (III and IV).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Most studies in this review found that Moesin was strongly associated with the histopathological grading for cancer[ 6 8 9 16 18 26 ] but was not elicited in a study[ 17 ] done in Baghdad where no statistical significance was elicited between the expression of Moesin and its association with the histopathological grading in OSCC cases. In a study[ 26 ] on laryngeal squamous cell carcinoma (LSCC), Moesin expression did not show any association with the advanced clinical staging (III and IV).…”
Section: Discussionmentioning
confidence: 95%
“…Most of the studies were cross-sectional and were conducted in university hospitals, cancer hospitals, or tertiary care centers. [ 6 9 16 17 18 20 27 ] The tissues samples were stereotypically collected from male patients, more than 55 years of age, and at least 40% of the samples showed marked expression of Moesin in their cytoplasm [ Table 1 ].…”
Section: Resultsmentioning
confidence: 99%